Fra studienummer til hyrde for en menighed - Hjort, Birgitte Graakjær; Hedelund, Jonas Midtgaard (Dansk Teologisk Tidsskrift, 2024)
According to Danish legislation theological candidates need to be examined by a bishop prior to ordination. The bishop’s examination in the Evangelical-Lutheran Church in Denmark is part of the episcopal oversight. The article analyses the bishops’ theological reflections and practical experiences with episcopal examinations based on interviews. According to our Aristotelian analysis of interviews the bishops operate with a distinction between different forms of knowledge that reflects the Aristotelian epistêmê, technê and phronêsis. While candidates may not pass, instances are rare; typically, guidance or resubmission is offered if the bishop hesitates to give collats. In addition to our Aristotelian analysis, we consider a management theoretical perspective on the interviews, and this perspective shows that the bishops align closely with Lotte S. Lüscher’s definition of a postmodern paradigm of management. Further, we argue that Jürgen Habermas’ focus on a potential shift in a conversation might elucidate dynamics in the conversation between bishop and candidate. The power relationship is camouflaged in the form of conversation, and Habermas’ theory helps us to understand when the power relationship manifests itself.